2019
DOI: 10.3389/fphar.2019.00981
|View full text |Cite
|
Sign up to set email alerts
|

Situation, Impacts, and Future Challenges of Tobacco Control Policies for Youth: An Explorative Systematic Policy Review

Abstract: Background: Tobacco use in youths is a major public health challenge globally, and approaches to the challenge have not been sufficiently addressed. The existing policies for tobacco control are not well specified by age. Objective: Our study aims to systematically investigate existing tobacco control policies, potential impacts, and national and international challenges to control tobacco use targeting the youth. Data sources: We used the statistics of the Global Youth Tobacco Survey (GYTS), studies, and appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 90 publications
1
23
0
1
Order By: Relevance
“…Previous studies have shown that restricting home smoking reduces the urine cotinine levels [ 24 , 25 ], and this study also supports that finding. Restricting of home smoking is one of the popular tobacco control policies against children and youths’ exposure to tobacco [ 26 ]. However, in line with previous findings, the present study also verified that children in Korea living with smokers are exposed to tobacco products [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that restricting home smoking reduces the urine cotinine levels [ 24 , 25 ], and this study also supports that finding. Restricting of home smoking is one of the popular tobacco control policies against children and youths’ exposure to tobacco [ 26 ]. However, in line with previous findings, the present study also verified that children in Korea living with smokers are exposed to tobacco products [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tide of NCDs will increase demand for medical imaging, laboratory, outpatients and rehabilitation services [13] , [14] , [15] , [16] . Therefore, health promotional activities to promote active lifestyle and healthy diet, improving access to preventive services, [54] and enacting and monitoring policies (tobacco control) [55] must go hand in hand with increased investment in modern medical technologies and education and training of health workers [56] . The LMICs share of the total health expenditure (THE) increased from 10.7% in 1995 to 14.6% in 2013, during the same period, the medical spending out of total THE increased from 26.1% to 39.7%, indicating health systems in LMICs to experience fiscal challenges to meet the demand for medical services [57] .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is associated with several diseases, such as chronic obstructive pulmonary disease, cardiovascular disease, lung cancer, and other cancers ( 2 4 ). Therefore, most countries, including Sweden, have adopted restrictive policies on tobacco sales and tobacco use ( 5 – 8 ). Smoking at an early age when the brain is under development is particularly harmful and associated with being an adult smoker ( 9 13 ).…”
Section: Introductionmentioning
confidence: 99%